Anaesthetic Management of Patient with Limb Girdle Muscular Dystrophy Scheduled for Laparoscopic Cholecystectomy - Shakya, Bigen Man; Shrestha, Shrastha (Nepal Journal of Medical Sciences, 2023)
The multiple anaesthetic concerns in a patient with Limb-Girdle muscular dystrophy make the anaesthetic management of the patient difficult. It can be safely managed with adequate pre-operative assessment and careful choice of anaesthetic agents. Our case was managed with general anaesthesia using a short-acting opioid, total Intravenous anaesthesia with propofol and dexmedetomidine avoiding muscle relaxant.